2005
DOI: 10.1126/science.1115109
|View full text |Cite
|
Sign up to set email alerts
|

Contact-Dependent Inhibition of Growth in Escherichia coli

Abstract: Bacteria have developed mechanisms to communicate and compete with each other for limited environmental resources. We found that certain Escherichia coli, including uropathogenic strains, contained a bacterial growth-inhibition system that uses direct cell-to-cell contact. Inhibition was conditional, dependent upon the growth state of the inhibitory cell and the pili expression state of the target cell. Both a large cell-surface protein designated Contact-dependent inhibitor A (CdiA) and two-partner secretion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
509
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(527 citation statements)
references
References 16 publications
6
509
2
1
Order By: Relevance
“…1A). This result suggested that CFT073 could prevent MG1655 FЈ biofilm formation, either by direct contact or secretion of an inhibitory molecule (14,15). To distinguish between these two possibilities, we conducted in vitro adhesion assays in poly(vinyl chloride) microtiter plates and microfermentors, containing filtersterilized CFT073 supernatant of a stationary phase culture.…”
Section: Cft073mentioning
confidence: 99%
“…1A). This result suggested that CFT073 could prevent MG1655 FЈ biofilm formation, either by direct contact or secretion of an inhibitory molecule (14,15). To distinguish between these two possibilities, we conducted in vitro adhesion assays in poly(vinyl chloride) microtiter plates and microfermentors, containing filtersterilized CFT073 supernatant of a stationary phase culture.…”
Section: Cft073mentioning
confidence: 99%
“…PAI I-III and V contain genes that either are absent in strain CFT073 [e.g., several adhesin gene clusters and the cdiAB genes required for contact-dependent growth inhibition of other bacteria (22)] or which are located in similar islands located elsewhere in the CFT073 genome. PAI IV is very similar in both UPEC strains.…”
Section: E Coli 536 Genome Sequence Determination and Comparative Anal-mentioning
confidence: 99%
“…The underlying mechanisms by which cells are inhibited in the SCDI reported here and the CDI reported by Aoki et al (2005) have not yet been elucidated. However, it is clear that these two inhibitory processes are functionally and genetically distinct.…”
Section: Discussionmentioning
confidence: 87%
“…How important the CDI reported by Aoki et al (2005) and that observed in this study are to the ecology of bacteria is unclear at this time but is certainly intriguing and worthy of further investigation. If in natural populations CDI and SCDI have effects of the magnitude observed in these laboratory studies, they could have a profound effect on the structure of bacterial communities.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation